Outcomes of laboratory-confirmed SARS-CoV-2 infection during resurgence driven by Omicron lineages BA.4 and BA.5 compared with previous waves in the Western Cape Province, South Africa. (February 2023) - Davies, Mary-Ann; Morden, Erna; Rousseau, Petro; Arendse, Juanita; Bam, Jamy-Lee; Boloko, Linda; Cloete, Keith; Cohen, Cheryl; Chetty, Nicole; Dane, Pierre; Heekes, Alexa; Hsiao, Nei-Yuan; et al.
Highlights: Severe hospitalization or risk of death was similar for BA.4/BA.5 and BA.1 infections. Previous infection and vaccination strongly protected against severe COVID-19. Growing population immunity against COVID-19 resulted in reduced severe disease. Booster vaccinations are important to reduce the public health impact of COVID-19. Abstract: Objectives: We aimed to compare the clinical severity of Omicron BA.4/BA.5 infection with BA.1 and earlier variant infections among laboratory-confirmed SARS-CoV-2 cases in the Western Cape, South Africa, using timing of infection to infer the lineage/variant causing infection. Methods: We included public sector patients aged ≥20 years with laboratory-confirmed COVID-19 between May 01-May 21, 2022 (BA.4/BA.5 wave) and equivalent previous wave periods. We compared the risk between waves of (i) death and (ii) severe hospitalization/death (all within 21 days of diagnosis) using Cox regression adjusted for demographics, comorbidities, admission pressure, vaccination, and previous infection. Results: Among 3793 patients from the BA.4/BA.5 wave and 190, 836 patients from previous waves, the risk of severe hospitalization/death was similar in the BA.4/BA.5 and BA.1 waves (adjusted hazard ratio [aHR] 1.12; 95% confidence interval [CI] 0.93; 1.34). Both Omicron waves had a lower risk of severe outcomes than previous waves. Previous infection (aHR 0.29, 95% CI 0.24; 0.36) and vaccination (aHR 0.17; 95% CI 0.07; 0.40 for at least three doses vs no vaccine) were protective. Conclusion: Disease severity was similar among diagnosed COVID-19 cases in the BA.4/BA.5 and BA.1 periods in the context of growing immunity against SARS-CoV-2 due to previous infection and vaccination, both of which were strongly protective.